Governance of Social Assistance Budget Realization and Its Impact on Regional Macroeconomic Performance in Indonesia (Study of 34 Provinces, 2018–2023) - Mimip Miptahudin; Hady Sutjipto; Sugeng Setyadi (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
This study analyzes the effects of social assistance budget realization, per capita income, and provincial minimum wage on poverty, open unemployment, and income inequality across 34 Indonesian provinces from 2018 to 2023. The research employs the Generalized Method of Moments (GMM) using panel data to address endogeneity and heteroskedasticity issues. Data were obtained from the Central Statistics Agency (BPS) and National Development Planning Agency (Bappenas). The results show that social assistance has a negative and significant impact on poverty and unemployment, but a positive and insignificant effect on inequality. Per capita income negatively affects poverty, positively influences unemployment, and has an insignificant negative impact on inequality, while provincial minimum wage significantly reduces unemployment but shows no significant effect on poverty and inequality. These findings indicate that fiscal social policies are effective in reducing poverty and unemployment but have limited impact on income disparity. Strengthening targeting accuracy and policy integration is essential to promote inclusive economic growth in Indonesia.